2015
DOI: 10.7554/elife.05216
|View full text |Cite
|
Sign up to set email alerts
|

Eye morphogenesis driven by epithelial flow into the optic cup facilitated by modulation of bone morphogenetic protein

Abstract: The hemispheric, bi-layered optic cup forms from an oval optic vesicle during early vertebrate eye development through major morphological transformations. The overall basal surface, facing the developing lens, is increasing, while, at the same time, the space basally occupied by individual cells is decreasing. This cannot be explained by the classical view of eye development. Using zebrafish (Danio rerio) as a model, we show that the lens-averted epithelium functions as a reservoir that contributes to the gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
211
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(227 citation statements)
references
References 41 publications
16
211
0
Order By: Relevance
“…We were able to induce eye-specific loss of pigmentation by expressing our transgene exclusively in the progenitors of the neural retina and the retinal-pigmented epithelium (RPE). For this purpose we used a transgenic line, Tg(rx2:gal4), in which the Gal4 trans-activator is specifically driven in the optic primordium by the promoter of the zebrafish retinal homeobox gene 2 (rx2; Heermann et al 2015). This result confirmed the ability of our strategy to induce Gal4-and Cas9-mediated tissue-specific gene inactivation.…”
Section: Crispr/cas9 and Gal4/uas Combination For Cell-specific Gene supporting
confidence: 59%
“…We were able to induce eye-specific loss of pigmentation by expressing our transgene exclusively in the progenitors of the neural retina and the retinal-pigmented epithelium (RPE). For this purpose we used a transgenic line, Tg(rx2:gal4), in which the Gal4 trans-activator is specifically driven in the optic primordium by the promoter of the zebrafish retinal homeobox gene 2 (rx2; Heermann et al 2015). This result confirmed the ability of our strategy to induce Gal4-and Cas9-mediated tissue-specific gene inactivation.…”
Section: Crispr/cas9 and Gal4/uas Combination For Cell-specific Gene supporting
confidence: 59%
“…As seen in vivo, invagination started at the side opposite the fissure, and fissure formation was coupled with the polarized invagination processes. In vertebrate retinal development, it has been thought that the optic fissure is formed by folding of the ventral retinal epithelium (Heermann et al, 2015); however, there are no reports showing a detailed process of optic fissure formation by live imaging. Furthermore, it has previously been shown that increased cell proliferation and extensive apoptosis in the ventral optic vesicle might accompany optic fissure formation (Ozeki et al, 2000;Trousse et al, 2001;Morcillo et al, 2006), and in a Bmp7 mutant mouse, fissure formation was not initiated (Morcillo et al, 2006).…”
Section: D-v Morphogenesis In Esc-derived Optic Cupmentioning
confidence: 99%
“…Subsequently, we tested whether spatiotemporally regulated tyr loss-of-function can be induced by our vector system. For this purpose, we used a transgenic line expressing Gal4 under the promoter of the zebrafish retinal homeobox gene 2 (rx2) (Heermann et al 2015), Tg(rx2:Gal4;myl7:GFP). We identified transgenic embryos using the myl7 (myosin, light chain 7, regulatory) promoter, driving heart-specific GFP expression, which was incorporated in the same transgene.…”
Section: Resultsmentioning
confidence: 99%
“…As a single efficient sgRNA could be identified for this gene, the same target sequence was inserted downstream from each of the two U6 promoters. We chose the rx2:Gal4 driver to express this UAS construct targeting pvalb6 in multipotent retinal progenitor cells as the rx2 promoter is active during early eye field development (Chuang and Raymond 2001;Heermann et al 2015). It has been previously reported that one single RPC can give rise to clones including all of the different retinal cell types spanning all retinal layers (Livesey and Cepko 2001).…”
Section: Visualizing 2c-cas9-mediated Gene Inactivationmentioning
confidence: 99%
See 1 more Smart Citation